Pengaruh Pembelajaran E-Learning Berbasis Media Sosial Terhadap Motivasi Belajar Siswa Kelas IV SDN Sindangwangi 03 Kabupaten Brebes - Intan Anggraeni; Ferina Agustini; Fine Reffiane (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to determine the effect of social media-based e-learning on  motivation of fourth grade students of SDN Sindangwangi 03, Brebes. This type of research uses quantitative research methods, with a Pre Experimental Design model in the form of one group pretest-posttest design. The data study were obtained through interviews, questionnaires and documentation. Based on the results of data analysis, it is known that the average score of students 'final motivation is higher than the average score of students' initial motivation (80.708> 39.583. While the average result of the final motivation score filled in by parents is higher than the average initial motivation score (82,500 > 41,417). The results of the one-party t-test analysis were obtained t-count amounting to 26,508 and t-table amounting to 1,714. and a significant level of 0.05, because t-count > t-table namely 26,508  1,714 so that h0 rejected ha accepted. While the results of the t-test calculation of the students' parent / guardian questionnaire were obtained t-count amounting to 30,429 and t-table amounted to 1,714. and a significant level of 0.05, because because t-count > t-table namely 30,429 1,714. so that h0 rejected ha accepted. meaning that there is an effect of social media-based E-Learning on learning motivation of fourth grade students of SDN Sindangwangi 03, Brebes Regency.